Major Late Cretaceous Mass Flows in Central Turkey Recording the Disruption of the Mesozoic Continental Margin. Issue 3 (18th March 2019) - Okay, Aral I.; Altıner, Demir; Kylander‐Clark, Andrew R. C.
Abstract: The newly recognized Upper Cretaceous (~87 Ma) olistostrome belt in central Turkey west of Ankara extends for more than 112 km subparallel to the Izmir‐Ankara suture with a width of 10 km. The Alacaatlı Olistostromes are stratigraphically underlain by a Triassic basement, and are up to 2 km thick. Over 80% of the blocks in the olistostromes consist of pelagic limestones, which reach up to 300 m in size; other blocks include basalt, chert, serpentinite, tuff, and sandstone. The limestone blocks are Jurassic and Cretaceous in age with micropaleontology documenting the presence of Callovian‐Oxfordian, Tithonian, Berriasian, Aptian, Albian, Cenomanian, and Turonian stages. The flows are separated by intrabasinal sediments of shale, siltstone, and volcaniclastic sandstone with Albian (108–101 Ma) detrital zircons. The olistostromes show minor tectonic deformation, and are unconformably overlain by Santonian pelagic limestones. The deposition of the Alacaatlı Olistostromes was followed by arc magmatism, which started in the Campanian (~78 Ma) after a period of shortening and uplift, and the region became a fore‐arc basin with deposition of shale and volcaniclastic sandstone with Campanian (78–72 Ma) detrital zircons. A number of peculiar features of these olistostromes including rapid uplift and erosion before the creation of a deep, short‐lived (89–86 Ma) ephemeral basin, dominance of deep marine limestone blocks, and inception of arc magmatism approximately 9 Myr after their deposition indicate a major tectonic event involving the disruption of the continental margin prior to the onset of arc magmatism. This event is interpreted as a change from transform margin to subduction. Key Points: A belt of Upper Cretaceous (approximately 87 Ma) olistostromes, >112 km‐long and 2 km in stratigraphic thickness, crops out in central Turkey The olistostromes contain Jurassic and Cretaceous pelagic limestone and ophiolite blocks and rest stratigraphically on a Triassic basement Disruption of the continental margin during a change from transform to subduction was responsible for the formation of the mass flows